A Statistical Study of F‐Region 3.2‐m‐Scale Field‐Aligned Irregularities Occurrence and Vertical Plasma Drift Over Hainan: Solar Activity, Season, and Magnetic Activity Dependences. Issue 5 (7th May 2021) - Jin, Han; Zou, Shasha; Yan, Chunxiao; Yang, Guotao; Chen, Gang; Zhang, Shaodong; Yan, Jingye; Yi, Shan; Wang, Zhihua
Abstract: The dependences of the nighttime low‐latitude F‐region 3.2‐m‐scale field‐aligned irregularities (FAIs) occurrence and vertical drift on solar activity, season, and magnetic activity during 2014–2017 are studied by using the coherent scatter radar located at Fuke (19.5°N, 109.1°E) and a nearby Digisonde at Sanya (18.4°N, 109.6°E), Hainan Island, China. The postsunset FAIs occurrence and vertical drift are closely related and modulated by the solar activity, especially for equinox. Utilizing the day‐to‐day comparison analysis, the threshold of the peak V z for the definitive postsunset FAIs generation during equinox was ∼30 m/s. The postmidnight FAIs occurrence in June solstice did not increase with the decreasing solar activity and is different from the nearby longitude 100°E reported by other studies. This difference is suggested to be due to the different Intertropical Convergence Zone activity between the two longitudes and reveals the highly localized and dynamic nature of irregularities, which clearly highlights the related challenges of space weather forecast. The SYM‐H and AE indices are used as indicators of the geomagnetic activity level, and the statistical results show that enhanced geomagnetic activity appears to weaken the evening V z and thus suppress the subsequent FAIs generation during the postsunset period. Westward substorm‐related overshielding electric field and/or disturbance dynamo electric field in the dusk side are suggested to play a role in the FAIs suppression during geomagnetic disturbances. This study contributes to the limited available statistical results in the Asian sector and is valuable for the holistic understanding of the global small‐scale FAIs occurrence pattern. Key Points: Solar flux and seasonal variations of field‐aligned irregularities (FAIs) occurrence rate are controlled by the vertical drift velocity pattern Abnormally low postmidnight FAIs occurrence rate in June solstice under low solar flux is attributed to the inactive Intertropical Convergence Zone around 110°E Enhanced geomagnetic activity tends to weaken the upward drift velocity and suppress the FAIs generation over Hainan in the dusk side